Human Immunodeficiency Virus (HIV): Epidemiology, Prevention, and Management Challenges in Indonesia - Irawan, Ade; Putra, Teguh Adiyas (Jurnal Medisci, 2025)
Background. Human Immunodeficiency Virus (HIV) is one of the global public health problems that is still a serious challenge, including in Indonesia. HIV infection causes a decrease in the immune system, which leads to Acquired Immunodeficiency Syndrome (AIDS) if not treated appropriately. Purpose. This article aims to examine the development of HIV epidemiology, risk factors for transmission, prevention strategies, and HIV management efforts in Indonesia, based on a recent scientific literature review. Method. The method used is a literature study of relevant national and international journal articles. Results. The results of the study show that the increase in HIV cases is influenced by risky behaviors, low access to tests and therapies, and stigma and discrimination against People With HIV/AIDS (ODHA). Prevention efforts through HIV education, testing, and counseling, and antiretroviral therapy (ARV) have proven effective in reducing the rate of transmission. Conclusion. In conclusion, HIV control requires a multidisciplinary approach that involves medical, social, and health policy aspects.